Maternal smoking during pregnancy and criminal offending among adult offspring. Issue 12 (15th November 2010) - Paradis, Angela D; Fitzmaurice, Garrett M; Koenen, Karestan C; Buka, Stephen L
Abstract : Background: Although a number of previous studies have reported an association between maternal smoking during pregnancy (MSP) and externalising behaviour problems among offspring, it has been suggested that this relationship is spurious due to the failure of these studies to properly account for important confounding factors. Methods: The relationship between MSP and adult criminal offending was examined using data from 3766 members of the Providence, Rhode Island, cohort of the Collaborative Perinatal Project. Information on MSP and most potential confounders was collected prospectively throughout pregnancy. In 1999–2000 all offspring had reached 33 years of age and an adult criminal record check was performed. Because previous research has been criticised for not properly accounting for confounding influences, our primary aim was to determine whether the MSP–criminal offending relationship held after efficiently adjusting for a wide range of sociodemographic and family background characteristics using propensity score methods. Results: The association between MSP and adult criminal offending remained after controlling for propensity scores. Offspring of mothers who smoked heavily during pregnancy (≥20 cigarettes per day) had the greatest odds of an adult arrest record (OR 1.31, 95% CI 1.06 to 1.62). Findings also suggest that MSP may be an independent risk factor for adult criminal histories marked by multiple arrests. Lastly, our findings show that the impact of MSP operates similarly across both genders. Conclusion: Results from this study provide evidence of an association between heavy MSP and long-term criminal offending. Any causal association is likely to be weak to moderate in strength.